Conditions Necessary for the Transfer of Antimicrobial Resistance in Poultry Litter - Aaron Oxendine; Allison A. Walsh; Tamesha Young; Brandan Dixon; Alexa Hoke; Eda Erdogan Rogers; Margie D. Lee; John J. Maurer (MDPI AG, 2023)
Animal manures contain a large and diverse reservoir of antimicrobial resistance (AMR) genes that could potentially spillover into the general population through transfer of AMR to antibiotic-susceptible pathogens. The ability of poultry litter microbiota to transmit AMR was examined in this study. Abundance of phenotypic AMR was assessed for litter microbiota to the antibiotics: ampicillin (Ap; 25 μg/mL), chloramphenicol (Cm; 25 μg/mL), streptomycin (Sm; 100 μg/mL), and tetracycline (Tc; 25 μg/mL). qPCR was used to estimate gene load of streptomycin-resistance and sulfonamide-resistance genes aadA1 and sul1, respectively, in the poultry litter community. AMR gene load was determined relative to total bacterial abundance using 16S rRNA qPCR. Poultry litter contained 108 CFU/g, with Gram-negative enterics representing a minor population (<104 CFU/g). There was high abundance of resistance to Sm (106 to 107 CFU/g) and Tc (106 to 107 CFU/g) and a sizeable antimicrobial-resistance gene load in regards to gene copies per bacterial genome (aadA1: 0.0001-0.0060 and sul1: 0.0355-0.2455). While plasmid transfer was observed from Escherichia coli R100, as an F-plasmid donor control, to the Salmonella recipient in vitro, no AMR Salmonella were detected in a poultry litter microcosm with the inclusion of E. coli R100. Confirmatory experiments showed that isolated poultry litter bacteria were not interfering with plasmid transfer in filter matings. As no R100 transfer was observed at 25 °C, conjugative plasmid pRSA was chosen for its high plasmid transfer frequency (10−4 to 10−5) at 25 °C. While E. coli strain background influenced the persistence of pRSA in poultry litter, no plasmid transfer to Salmonella was ever observed. Although poultry litter microbiota contains a significant AMR gene load, potential to transmit resistance is low under conditions commonly used to assess plasmid conjugation.